The parental language policy on children's language acquisition: a case of international family - Faridatul Istighfaroh; Sonny Elfiyanto; M. Faruq Ubaidillah (Journal on English as a Foreign Language, 2023)
Discussing second language acquisition (SLA) from the perspective of one same-nationality family has been massively conducted. However, the recent study regarding SLA in toddlers in mixed-marriage families, especially with Indonesian mothers, has not been previously observed. Directed to the study demonstrated by Li (2007), this present study aimed to examine the three essential marks of family roles on their children's acquisition, such as the parent's literacy accomplishment, the daily occupation choice and opportunity, and adaptation as well as integration into the local country. Two families with Sudan-Indonesia and America-Indonesia backgrounds participated as research subjects. The narrative inquiry method through interviews (see Duff, 2019) was employed to gain the data. Then, the data were analyzed by using Braun and Clarke’s (2006) six thematic analysis stages. The results revealed that the parental academic records of accomplishment, the family's occupation, and the socialization to the domestic environment positively affected family language policy (FLP), shaping the stairs of children's SLA. Moreover, this study may contribute to Indonesian families, school stakeholders, and EFL teachers in teaching the foreign language to their children and EFL students in gaining new languages.